Isopropyl Alcohol Purification through Extractive Distillation using Glycerol as an Entrainer: Technical Performances Simulation and Design (Jurnal Bahan Alam Terbarukan, 2019)
Isopropyl alcohol is widely used as industrial chemical intermediates and common solvents in households, pharmaceuticals, food, cosmetics, and medical purposes. The high purity of isopropyl alcohol requires special separation from its impurity i.e. water due to isopropyl alcohol and water form an azeotropic point, which is difficult to separate using a conventional distillation method. The azeotropic point of this mixture is at isopropyl alcohol mole fraction of 0.68 and temperature of 353.4 K. One of the optimum methods to separate an azeotrope point is through the extractive distillation which use a third component as a solvent. Glycerol is one of the solvents which can be used as a potential entrainer in the extractive distillation. Glycerol is produced in the biodiesel production as a by-product. Moreover, glycerol is an eco-friendly chemical. In this work, the simulation of the extractive distillation of isopropyl alcohol/water system with glycerol as an entrainer was simulated using Aspen Plus. The Non-Random Two-Liquid (NRTL) model was used as thermodynamic model in the simulation. Â The effect of stage number, binary feed stage, entrainer feed stage, and reflux ratio to the purity of isopropyl alcohol, and reboiler-condenser duties were examined to achieve the optimum design for the extractive distillation column with less energy requirements. The simulation results showed that the optimum configurations in the extractive distillation column design are at 25 theoretical stages, binary feed stage (BFS) of 20, entrainer feed stage (EFS) of 2, and reflux ratio (RR) of 0.5 to produce isopropyl alcohol with the purity of 99.27%. The design and sizing of the extractive distillation column were also proposed in this work.